Effects of seat height on whole-body movement and lower limb muscle power during sit-to-stand movements in young and older individuals. (2nd December 2021) - Honda, Keita; Sekiguchi, Yusuke; Sasaki, Akiko; Shimazaki, Satoko; Suzuki, Rie; Suzuki, Takahiro; Kanetaka, Hiroyasu; Izumi, Shin-Ichi
Abstract: Sit-to-stand (STS) movements from low seat height are not easily executed by older individuals. Although young individuals increase their lower limb muscle power (LLMP) based on the product of the ground reaction force (GRF) and center of mass velocity (CoMv) during STS movement from a low seat height, it remains unclear whether seat height has an effect on LLMP during STS movement in older individuals. The present study aimed to investigate differences in the LLMP during STS movements when seat height is lowered between young and older individuals. Twelve older and twelve height-matched young individuals were instructed to perform STS movements from low (20 cm), middle (40 cm), and high (60 cm) seat heights. STS movement and GRF were obtained by a motion analysis system and force plates. In the low-seat-height condition, the forward and upward LLMPs and the upward CoMv were significantly lower in older individuals than those in young individuals, but the forward CoMv was not. The completion time of STS movement from a low seat height was significantly longer in older individuals than in young individuals. Our findings suggest that the slower upward CoMv due to the lower upward LLMP extends the completion time of STS movement from a low seat height in older individuals. Furthermore, in the low-seat-height condition, older individuals may move their center of mass (CoM) forward in a different way when compared with young individuals, and they may not use forward LLMP for moving CoM forward.